2015
DOI: 10.1016/j.worlddev.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Using Agriculture to Improve Child Health: Promoting Orange Sweet Potatoes Reduces Diarrhea

Abstract: Vitamin A deficiency (VAD) is prevalent throughout the developing world, and causes night blindness and increases child morbidity and mortality. We studied the health benefits of biofortification in reducing VAD, using a cluster-randomized impact evaluation in 36 villages in northern Mozambique. Based on a sample of 1,321 observations of children under the age 5, biofortification reduced diarrhea prevalence by 11.4 percentage points (95% CI 2.0-20.8), and by 18.9 percentage points in children under the age thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 28 publications
1
69
0
Order By: Relevance
“…Previous OFSP-focused strategies in Uganda and Mozambique improved child VA intakes and status (1, 2) and reduced child diarrhea (33). Maternal VA intakes also increased (2); however, impacts on other maternal health and nutrition indicators were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous OFSP-focused strategies in Uganda and Mozambique improved child VA intakes and status (1, 2) and reduced child diarrhea (33). Maternal VA intakes also increased (2); however, impacts on other maternal health and nutrition indicators were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Palmer et al [14] demonstrated improved pupillary responsiveness through consumption of provitamin A carotenoid-biofortified maize, while Jones and de Brauw [15] showed promising evidence of orange sweet potato in reducing childhood diarrhoea. While these crop-based interventions have proven to have substantive benefits, to date they have mostly targeted replacement of single micronutrients [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among children who consumed OSP, the prevalence of diarrhea was 11.5 percentage points lower for children younger than five, and 19 percentage points lower for children younger than three, compared with children who did not consume OSP. Similarly, children who consumed OSP suffered from less diarrhea-0.6 days (for those younger than five) to 1.3 days (for those younger than three) less per week-than children who did not consume OSP (Jones and de Brauw 2015). These results reveal that biofortification could improve child health (Jones and de Brauw 2015).…”
Section: Current Evidence: Nutrition Impactmentioning
confidence: 84%
“…In Mozambique, the delivery of OSP doubled vitamin A intakes, with OSP providing almost the entire total vitamin A intake for children (Hotz et al 2012a). Consumption of OSP also reduced the prevalence and duration of diarrhea among children (Jones and de Brauw 2015). Among children who consumed OSP, the prevalence of diarrhea was 11.5 percentage points lower for children younger than five, and 19 percentage points lower for children younger than three, compared with children who did not consume OSP.…”
Section: Current Evidence: Nutrition Impactmentioning
confidence: 88%
See 1 more Smart Citation